Mediation of Entrepreneurial Motivation: The Role of Entrepreneur Learning, Self-Efficacy and Family Environment in Increasing Interest in Entrepreneurship - Martini, Ida Ayu Oka; Sari, Desak Made Febri Purnama; Sarmawa, I Wayan Gde; Qomariah, Nurul; Ridwan, Wachid (Universitas Brawijaya, Indonesia, 2024)
The recovery period from the COVID-19 pandemic has stimulated the acceleration of economic recovery in Indonesia, but the availability of job opportunities is still not optimal. In response, students' entrepreneurial interests must always be improved. The aim of this research is to analyze the influence of entrepreneurial learning, self-efficacy, and family environment, motivation and entrepreneurial interest. This research was designed as quantitative research with a causal type of research. The population in this research was all Denpasar Bali Private University students, with a sample of 250 students. The sampling technique uses purposive random sampling. The data in this research was obtained through a survey method using a questionnaire. The data analysis technique uses partial least squares. The research results show that entrepreneurial learning, self-efficacy, and family environment have a significant effect on entrepreneurial motivation. Likewise, self-efficacy, family environment, and entrepreneurial motivation also have a significant influence on entrepreneurial interest. However, entrepreneurial learning does not have a significant influence. Entrepreneurial motivation can act as a mediator in the influence of family environment on entrepreneurial interest but not on entrepreneurial learning and self-efficacy. It is hoped that this research can become a reference for the Government to develop strategies to fulfill the target of an entrepreneurial ratio of at least 4% of the population in order to accelerate Indonesia to become a developed country by 2045.